The Effect of Bank-Specific and Macro-Economic Variables on Bank Profitability: Case of USA. - Asobo, Elvis Awa (Eastern Mediterranean University EMU, 2017)
The main aim of this thesis is to determine the effect of both bank-specific and macro-economic variables on the profitability of the US banking sector. In order to accomplish this, ROA and ROE were considered as profitability indicators while bank size, liquidity, capital adequacy, assets quality, interest rate, inflation rate and gross domestic product where considered as independent variables. This study uses fifteen US banks ranked according to total assets from 2001 to 2015. During the period for this study, US encountered a devastating financial crisis that affected the whole financial sector. In order to capture the effect of this crisis, I introduced a dummy variable for the crisis period from 2007 to 2010. When the regression analysis was done considering ROA as the dependent variable, bank size and assets quality were negative and significant. Interest rate and GDP growth were positive and significant while inflation, capital adequacy and liquidity where insignificant. Using ROE as dependent variable, capital adequacy became significant and the other results remained the same. Keywords: Bank Profitability, USA, Liquidity, Capital Adequacy, Financial Crises

ÖZ: Bu tezin temel amacı hem mikro hem de makro ekonomik değişkenlerin ABD bankacılık sektörü üzerindeki etkisini belirlemektir. Bunu sağlamak için ROA ve ROE, banka büyüklüğü, likidite, sermaye yeterliliği, varlık kalitesi, faiz oranı, enflasyon ve bağımsız değişken olarak düşünüldüğünde gayri safi yurtiçi hasıla olarak karlılık göstergeleri olarak düşünülmüştür. Bu çalışma, 2001 yılından 2015'e kadar toplam aktiflere göre sıralanan on beş Amerikan bankasını kullanmaktadır. Bu çalışma döneminde ABD, finansal sektörü etkileyen yıkıcı bir finansal krizle karşılaştı. Bu krizin etkisini yakalamak için kriz dönemi için 2007-2010 yılları arasında kukla bir Olarak kullandım. sundum. ROA'yi bağımlı değişken olarak dikkate alarak regresyon analizi yapıldığında, banka büyüklüğü ve varlık kalitesi negatif olarak karşımıza çıkmıştır. ve ölçeğin kaygılarını gösterdi. Faiz oranı ve GSYİH büyümesi Anlamlı olarak karşımıa çıkmıştır. ROE'yi bağımlı değişken kullandığımızda kullanarak sermaye yeterliliği önemli hale gelmiş diğer sonuçlarda farklılık gözlemlenmemiştir. Anahtar Kelimeler: Banka Kârlılığı, ABD, Likidite, Serameye Yeterliliği, Finansal Kriz
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2017. Supervisor: Assoc. Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance; Banks and Banking-United States; Bank Profitability; USA; Liquidity; Capital Adequacy; Financial Crises